Pengaruh Model Pembelajaran Deep Learning Berbantuan Genially terhadap Pemahaman Peserta Didik pada Mata Pelajaran Pendidikan Pancasila: Penelitian - R.R.Nyimas Ayu Nursukowati; Endang Danial; Dede Iswandi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of the deep learning model supported by the Genially platform on students' understanding of Pancasila Education. The background of this study is based on the low student learning outcomes due to the dominance of conventional methods that minimize interaction and active participation. The study used a quantitative approach with a quasi-experimental method, involving two seventh grade classes at SMP Negeri 29 Bandung. The experimental class received learning with the deep learning model supported by Genially, while the control class used the lecture method. Data were collected through pretests and posttests with multiple-choice objective test instruments. The analysis results showed a significant increase in student understanding in the experimental class. The average posttest score of the experimental class reached 80.5, an increase of 22.3 points from the pretest, while the control class increased by 12.167 points. The independent sample t-test showed a significance value of 0.047 (p < 0.05), indicating a significant difference between the two groups. In addition, the decrease in the standard deviation indicates an even distribution of student understanding. It can be concluded that the integration of the deep learning model and the Genially platform is effective in significantly improving student understanding.